Liver imaging with a novel Hepatitis B surface protein derived SPECT-tracer - Müller, Thomas; Mehrle, Stefan; Schieck, Alexa; Haberkorn, Uwe; Urban, Stephan; Mier, Walter (Molecular pharmaceutics, 2013)
Diagnostic imaging of the liver by ultrasound, computed tomography (CT) and magnetic resonance tomography (MRT) is generally limited to the visualization of the morphology. In order to exploit the intriguing liver tropism of the human hepatitis B virus (HBV) for molecular imaging of the liver, peptidic tracers derived from the HBV large envelope protein (L) were studied. An N-terminally stearoylated tracer comprising amino acids 2-48 of the PreS1-domain of the L protein was synthesized by solid phase peptide synthesis. Mercaptoacetyltriglycerin (MAG3) was linked to this peptide to enable 99mTc labeling. Biodistribution studies in mice showed an excellent liver accumulation of this novel class of radiotracer with 84%, 84%, 65%, and 16% of the injected dose in the liver after 10 min, 1 h, 4 h, and 24 h, respectively. Imaging studies on a gamma camera showed a clear visualization of the liver already 10 min post intravenous injection. These studies confirmed the exclusive accumulation of the tracer in the liver with negligible background in other organs. Owing to a significant biliary clearance rate of the 99mTc bound via a linker, the tracer enabled imaging of the bile ducts starting 30 min after injection. Analysis of the route of excretion revealed complete clearance within 24 h post injection. Clearance was predominantly via renal secretion. In conclusion, the novel class of tracers shows excellent pharmacokinetic, biodistribution, and clearance kinetics. It provides unique biological information different from the current imaging modalities. Its primary application is likely to be the evaluation of liver cancer patients. Specific indications may include tumor staging, the differentiation of malignant versus benign hepatic lesions, and liver tumors of nonhepatocellular origin.
Gesehen am 22.06.2021